Analysis of Factors Affecting Consumer Behavior towards Green Banking using TPB Model - Islam, Zohaib (Journal of Asian Business Strategy, 2022)
The purpose of this research paper is to analyze the factors which are affecting consumer behavior towards green banking. Alternatively, the research focuses on how customer’s attitude, subjective norms, and perceived behavioral control can play their role in the use and promotion of green banking. To analyze the data, this research paper follows the positivism philosophy therefore a quantitative approach is used to examine the problem by circulating a questionnaire among 263 people who are selected by using purposive sampling technique as the target audience was those people who have Bank account in Pakistan. The findings of this study support the previous results of the theory of planned behavior. Consumer attitude, subjective norms, and perceived behavioral control have a high effect on consumer intention to use green banking which shows that bank consumers in Pakistan are willing to use technology-driven banking practices if they are available. The result also supports past studies on attitude towards the adoption of internet and mobile banking in Pakistan. Our research can be helpful in developing an effective marketing strategy for the adoption of green banking. This study will help the government and marketers to create awareness regarding the benefits of using technology-driven eco-friendly banking practices so that consumers can learn about internet banking and start using it.